2023
DOI: 10.1093/cid/ciad258
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Colonization With Extended-Spectrum Cephalosporin-Resistant and Carbapenem-Resistant Enterobacterales Among Hospitalized Patients in Kenya: An Antibiotic Resistance in Communities and Hospitals (ARCH) Study

Abstract: Background The spread of extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE) and carbapenem-resistant Enterobacterales (CRE) represents a significant global public health threat. We identified putative risk factors for ESCrE and CRE colonization among patients in 1 urban and 3 rural hospitals in Kenya. Methods During a January 2019 and March 2020 cross-sectional study, stool samples were collected from randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“… 21 The presence of drug-resistant bacteria may be attributed to the antibiotic-related sequelae, similar to the selection pressure for resistant organisms or changes in the microbiome leading to dysbiosis and increased susceptibility to colonization. 22 In our study, we also found that a history of carbapenem administration increased the risk of 3GC-R E. coli BSI 2.05-fold, and for patients who received antimicrobial agents before blood culture, the risk increased 1.86-fold. Although receiving extended-spectrum antimicrobial agents may increase the incidence of 3GC-R E. coli , 1-hour or 3-hour regimens are still recommended for patients with severe BSIs.…”
Section: Discussionsupporting
confidence: 69%
“… 21 The presence of drug-resistant bacteria may be attributed to the antibiotic-related sequelae, similar to the selection pressure for resistant organisms or changes in the microbiome leading to dysbiosis and increased susceptibility to colonization. 22 In our study, we also found that a history of carbapenem administration increased the risk of 3GC-R E. coli BSI 2.05-fold, and for patients who received antimicrobial agents before blood culture, the risk increased 1.86-fold. Although receiving extended-spectrum antimicrobial agents may increase the incidence of 3GC-R E. coli , 1-hour or 3-hour regimens are still recommended for patients with severe BSIs.…”
Section: Discussionsupporting
confidence: 69%
“…Within the scope of our review, a solitary study conducted by Omulo et al (16) offered insights into CRE colonization among individuals living with HIV. Notably, this investigation revealed that the HIV status of participants does not exert a discernible impact on the carriage of CRE (Table 1).…”
Section: Carbapenem-resistant Enterobacterales Colonization and Human...mentioning
confidence: 99%
“…With global use rates increasing [ 8 , 9 ], including among outpatients [ 10 ], monitoring of populations at risk of carrying AMR bacteria is important, and can help to inform AMR control interventions. However, studies that have examined antibiotics use-resistance colonization relationship have yielded mixed results; observing associations in data rich regional- and national-level ecological designed studies [ 11 13 ], and some intercommunity and household-level studies [ 14 , 15 ], but rarely in data-limited global-level studies [ 16 18 ] and intracommunity studies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%